Trajetórias de escolarização: um estudo sobre egressos do curso técnico em economia doméstica - Manzan, William Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This paper presents the results of a research that examined gender issues in schooling trajectories of four graduates (two men and two women) Technical course in Home Economics, derived from the same public education establishment. The object of study analyzed consisted of the primary provisions of the relationships within gender, assimilated within their families and progenitor consolidating and restructuring the same formulation as the habitus of graduates in their school routes; in matrimonial strategies; in professional careers; cultural and social capital; and strategies for sex education and sexuality. Data collection took place between the period 2011 to 2012, was conducted through questionnaires and interviews with the selected graduates. The analysis used data from categories of method and analysis of Pierre Bourdieu to classification and assessment of the primary provisions that have manifested in a distributed manner in different contexts of the trajectories of the agents. Gendered provisions which necessarily became part and interact with the habitus of agents. After analyzing the categorization of accounts of life histories, it was observed that the habitus of gender restructured the trajectories of schooling continued directing and permeating the professional agents of social background and matrimonial strategies; it was noted also that the gendered habitus was shared by the social status of families constituted by agents and will now play in the offspring the same pattern of sex education strategy narrated in the period of childhood and youth of the same, ie, they stood historical regularities paternal silence and the division of the tract of sexuality as an educational action of the children between the mother figure and school agencies

O presente trabalho apresenta os resultados de uma pesquisa descritiva baseada no método praxiológico de Pierre Bourdieu, cuja investigação analisou questões de gênero nas trajetórias de escolarização de quatro egressos (dois homens e duas mulheres) do Curso Técnico em Economia Doméstica, todos oriundos e habilitados no mesmo estabelecimento público de ensino. O objeto de estudo constituiu-se de relações das disposições primárias, no âmbito de gênero, assimiladas no interior de suas famílias progenitoras e a consolidação das mesmas enquanto formulação e reestruturação do habitus dos egressos nos respectivos itinerários escolares; nas estratégias matrimoniais; nas trajetórias profissionais; no capital cultural e social; e nas estratégias de educação sexual e sexualidade. A coleta de dados realizada entre o período de 2011 a 2012, foi conduzida por meio da aplicação de questionários e da realização de entrevistas com os egressos selecionados. A análise de dados utilizou das categorias de método e análise de Pierre Bourdieu para classificação e apreciação das disposições primárias que se manifestaram de forma distribuída em diferentes contextos das trajetórias dos agentes. Disposições gendradas que necessariamente passaram a integrar e relacionar-se com o habitus dos agentes. Após a análise da categorização dos relatos das histórias de vida, observou-se que o habitus de gênero reestruturado pelas trajetórias de escolarização continuou orientando e permeando o percurso social e as estratégias matrimoniais e profissionais dos agentes. Notou-se, ainda, que o habitus gendrado foi compartilhado pelo estatuto social das famílias constituídas pelos agentes e que passaram a reproduzir, na prole, o mesmo padrão de estratégia de educação sexual narrado no período da infância e juventude dos mesmos, ou seja, conservou-se a regularidade histórica do silêncio paterno e a divisão do trato ...
Keywords: Escolarização; Economia domestica; Ensino tecnico; Ensino tecnico - Aspectos sociais; Technical education Social aspects